Rīgas Grebenščikova vecticībnieku draudzes darbība (1944.-1989.g.) - Novikova, Kristina (Latvijas Universitāte, 2012)
Maģistra darba „Rīgas Grebenščikova vecticībnieku draudzes darbība (1944.g.-1989.g.)” mērķis ir izpētīt Rīgas Grebenščikova vecticībnieku draudzes darbību laika posmā no 1944. līdz 1989.gadām. Hronoloģiskās robežas ir noteiktas pamatojoties uz padomju režīma īpatnībām. 1944.gadā Latvijas PSR tika izveidota PSRS Ministru Padomes Reliģijas kulta lietu padomes institūcija, kas pastāvēja līdz 1989.gadam Maģistra darbs sastāv no ievada, avotu un literatūras apskata, četrām nodaļām, secinājumiem, avotu un literatūras saraksta un pielikumiem. 1. nodaļā ir analizēti galvenie valsts un Baznīcas attiecību modeļi, totalitāro valsts pamatiezīmes, veidi, pamatprincipi un reliģiskā doktrīna. 2. nodaļā apskatīta padomju varas likumdošana, PSRS reliģiskās politikas pamatvirzieni, tika raksturota vietējās varas attieksme pret Baznīcu un vecticībnieku draudzēm laika posmā no 1944. līdz 1989. gadam. 3. nodaļā tika aplūkota Rīgas Grebenščikova vecticībnieku draudzes reliģiskā, kultūras, un saimnieciskā dzīve, tās galvenās problēmas un sasniegumi apskatāmā laika posmā. 4. nodaļā tiek analizēta Rīgas Grebenščikova vecticībnieku draudzes pārvaldes struktūras darbība 20.gs. 40.-80.-os gados. Tika secināts, ka J.Staļina valdīšanas laikā valsts mērķis bija mazināt reliģijas ietekmi sabiedrībā, nevis likvidēt to, savukārt, Ņ.Hruščova valdīšanas laikā sākās ideoloģiskā cīņa pret reliģiskām organizācijām. L.Brežņeva valdība izveidoja stingrās robežas un kontroli, kas reglamentēja reliģisko organizāciju darbību. 1980.-to gadu vidū, līdzās ar reliģijas lomas atdzimšanu sabiedrībā, valsts reliģiskā politika kļuva vērojami lojālāka. K.Čerņenko valdīšanas laikā tika mēģināts izveidot vēl stingrāku reliģijas kontroli. Valdības kurss sāka mainīties tikai ar M.Gorbačeva atnākšanu pie varas. Agrāk aizliegtas draudzes darbības jomas tika legalizētas, ka arī tika atceltas darbības robežas. Neskatoties uz reliģiskās politikas izmaiņām un valsts centieniem samazināt reliģisko draudžu skaitu, Rīgas Grebenščikova vecticībnieku draudze turpināja aktīvi attīstīties un darboties gan kultūras, gan reliģijas, gan saimniecības jomā, pieauga draudzes aktivitātes. Rīgas draudzes pārvaldes darbība arī netika sevišķi skārta no valsts puses, par ko liecina kopš 20.gs.sākuma saglabāta draudzes pārvaldes sistēma.

The goal of the master’s work “ Riga Grebenscikova Old Believer parish activities (years 1944-1989)” is to research the Riga Grebenscikova old believers’ congregation’s activities in the period between years 1944 through 1989. The chronological boundaries were set based on the peculiarities of the Soviet regime. The USSR Council of Ministers’ Religious cult council institution had been created in the Latvian SSR in 1944 and it existed until 1989. The master’s work consists of introduction, review of the sources and literature, four chapters, conclusions, the list of the sources and literature and appendices. The first chapter is utilized to analyze the major models of the relationship between the Church and the state, the key characteristics, types, basic principles and the religious doctrine of a totalitarian state. The second chapter is devoted to the overview of the Soviet legislation, the key directions of the USSR’s religious policies; the attitude of the local authorities with respect to the Church and the old believers’ congregations was described in the time period between 1944 and 1989. The third chapter surveys Riga Grebenscikova Old Believers’ congregation’s religious, cultural and economic life, its key problems and achievements in the timeframe under review. The fourth chapter is used to analyze the activities of the Riga Grebenscikova Old Believers’ congregation’s administrative structure between the ‘40’s and ‘80’s of the twentieth century. It has been concluded that during the time of the J. Stalin’s rule the goal of the state was to reduce the influence of the religion in the society, but no to abolish it completely, however, during the rule of N. Khrushchev, an ideological battle against the religious organizations began. The government led by L. Brezhnev developed strict boundaries and controls which regulated the work of religious organizations in the middle of the 1980’s; together with the resurgence of the role of the religion in the society, the policy of the state concerning religion became more loyal. During the rule of K. Chernenko an attempt was made to impose an even stricter control of religion. The government began to shift only when M. Gorbachev came to power. The fields of the congregation’s work formerly banned were legalized, limitations of activities were abolished. Despite the changes in the religious policies and the efforts of the government to reduce the number of the religious congregations, Riga Grebenscikova Old Believers’ congregation continued its active development and work both in the fields of culture, religion and economics; the activities of the congregation grew. The work of the Riga congregation council was also not substantially influenced by the state as evidenced by the administrative system of the congregation which has been preserved from the beginning of the 20th century.
The activities of the Riga Grebenshikova Old Believer parish (1944-1989)
Keywords: Vēsture